Active control of base drag through experimental investigation of a hybrid synthetic jet system: a comprehensive review - Asha, Afsana Hossain; Khan, Ambareen; Khan, Sher Afghan (medcraveonline, 2026)
Aerodynamic drag, particularly base drag generated by low-pressure wake regions, significantly impacts the fuel efficiency and emissions of bluff-bodied vehicles. While active flow control (AFC) methods like synthetic jets offer dynamic drag reduction, their practical application is often hindered by unproven net energy efficiency and limited integration with real-world vehicle geometries. This study experimentally investigates a novel hybrid aerodynamic system that synergistically combines recessed base cavity geometry with an array of piezoelectric synthetic jet actuators. The research aims to quantify the system’s efficacy in reducing base drag and, critically, to evaluate its net energy balance. Experiments were conducted on a scaled square-back Ahmed body model fitted with the hybrid system in a closed-circuit wind tunnel with moving ground simulation. Flow-field diagnostics were performed using particle image velocimetry (PIV) and direct force and base-pressure measurements. Results demonstrated that actuation tuned to the natural wake frequency (St ≈ 0.21) produced a 30% reduction in the recirculation zone, a 38% increase in base pressure, and an 11.2% net drag reduction. Crucially, the aerodynamic power saved exceeded the electrical power input to the actuators by a factor of 3.9, yielding a positive Net Energy Efficiency Ratio (NEER). This work concludes that a frequency-tuned hybrid synthetic jet system is a viable, energy-positive concept for reducing base drag. The study contributes a validated methodological framework for assessing AFC net efficiency and provides empirical evidence for the performance gains achievable through coupled active-passive design, offering a pathway toward sustainable transport aerodynamic solutions.